INTEGRASI SISTEM AKUNTANSI MANAJEMEN PENGGAJIAN DRIVER PADA PT. ADI SARANA ARMADA TBK (LOGISTICS) - Sukemi Kamto Sudibyo; Eni Endaryati; Vivi Kumalasari Subroto; Sri Wahyuning; Nur Rokhman; Agus Priyadi; Arga Adriansah (LPPM Politeknik Pratama, 2025)
Driver payroll management is a strategic aspect of financial management accounting because it not only accounts for a significant proportion of labor costs in logistics company operations but also directly relates to the well being of workers, the primary drivers of distribution. This study aims to analyze and design an integrated management accounting system that can improve the effectiveness, efficiency, and accuracy of driver payroll at PT Adi Sarana Armada Tbk. Using Research and Development (R&D) methods, the study was conducted in the logistics business unit through observation, interviews, and document review related to the existing payroll system. The results indicate that the integration of a digital based system accelerates the payroll process, increases transparency, and strengthens operational cost control. This system ensures salaries are paid fairly, on time, and according to regulations, while minimizing administrative errors. These findings underscore the importance of digital transformation as a managerial strategy to support operational performance and provide appropriate rewards to drivers, the primary drivers of logistics services.